STRENGHT BASED COUNSELING: ALTERNATIVE COUNSELING TO INCREASE WORKING STUDENTS' RESILIENCE - Oktasari, Maria; Ramli, M.; Hidayah, Nur (Universitas Indraprasta PGRI, 2024)
Resilience is a critical psychological capability, particularly for students who also work. Given the complexity of problems they encounter, working students must possess resilience to tackle challenges. Low resilience can lead to negative outcomes such as depression, anxiety, and stress. Therefore, interventions are necessary to enhance this resilience, one of which is through guidance and counseling services. One effective approach is strength-based counseling. This study employs a literature review method, drawing on data sources like Research Gate, Mendeley, and Google Scholar. This article discusses how counseling approaches that emphasize individual strengths and positive potentials can help improve the resilience of working students. The results indicate that strength-based counseling is effective in enhancing the resilience of working students. Strength-based counseling focuses on empowering individuals by utilizing the positive energy within themselves and their environment, rather than defining them based on problems or illnesses. Through this approach, working students can better manage the pressures and challenges they face, thereby improving their mental health and academic performance.